2018
DOI: 10.1029/2018jd029465
|View full text |Cite
|
Sign up to set email alerts
|

Validation of SOAR VIIRS Over‐Water Aerosol Retrievals and Context Within the Global Satellite Aerosol Data Record

Abstract: This study validates aerosol properties retrieved using a Satellite Ocean Aerosol Retrieval (SOAR) algorithm applied to Visible Infrared Imaging Radiometer Suite (VIIRS) measurements, from Version 1 of the VIIRS Deep Blue data set. SOAR is the over-water complement to the over-land Deep Blue algorithm and has two processing paths: globally, 95% of pixels are processed with the full retrieval algorithm, while the 5% of pixels in shallow or turbid (mostly coastal) waters are processed with a backup algorithm. Ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 106 publications
9
46
0
Order By: Relevance
“…The main metrics used here to evaluate the AAC retrievals, which are as often used in AOD validation exercises, including DB (e.g. Sayer et al, 2018bSayer et al, , 2019, are as follows.…”
Section: Validation Approachmentioning
confidence: 99%
“…The main metrics used here to evaluate the AAC retrievals, which are as often used in AOD validation exercises, including DB (e.g. Sayer et al, 2018bSayer et al, , 2019, are as follows.…”
Section: Validation Approachmentioning
confidence: 99%
“…Atmospheric aerosol emission inventories are often used to drive chemical transport model (CTM) simulations of aerosol distributions on regional and global scales (Boucher, 2015;Brasseur and Jacob, 2017;Granier et al, 2011). Satelliteretrieved columnar aerosol optical depth (AOD) is directly related to light extinction due to the presence of aerosols; hence, satellite-retrieved columnar AOD is widely used to evaluate the spatial and temporal variability of aerosols simulated from CTMs (e.g., Chin et al, 2002;Ginoux et al, 2006;Kinne et al, 2006Kinne et al, , 2003Liu et al, 2012;Ocko and Ginoux, 2017;Pozzer et al, 2015;Schulz et al, 2006;Tegen et al, 2019). A general agreement has been shown for columnar AOD between model simulations and satellite observations in the Aerosol Comparisons between Observations and Models (AeroCom) "Experiment A" multimodel assessments .…”
Section: Introductionmentioning
confidence: 99%
“…Using AOD observations from a set of 12 AERONET sites as reference, they concluded that no current technique uniformly performs best but that UNC values reported by MISR perform well at most sites. These recent studies by Sayer et al (2020) and Witek et al (2019) are the main motivations for comparing the reported UNC between V22 and V23 of the MISR aerosol product. Figure 8 compares the distributions of average MISR V22 and V23 UNC using retrievals from 2012.…”
Section: Aerosol Optical Depth (Aod) and Aod Uncertainty (Unc) Comparmentioning
confidence: 99%
“…They found that MISR-reported UNC realistically represent retrieval errors and the statistical behavior is similar to that of a Gaussian distribution. Sayer et al (2020) comprehensively reviewed current prognostic and diagnostic methods used for quantifying uncertainty in satellite AOD retrievals, outlined a general framework for evaluating their accuracy, and used the proposed approach to compare products from several satellite instruments, including MISR. Using AOD observations from a set of 12 AERONET sites as reference, they concluded that no current technique uniformly performs best but that UNC values reported by MISR perform well at most sites.…”
Section: Aerosol Optical Depth (Aod) and Aod Uncertainty (Unc) Comparmentioning
confidence: 99%